63‐1: Distinguished Student Paper: Microsecond High‐contrast Continuous 2.25π Phase Modulation Based on Non‐linear Kerr Effect of VADHFLC. Issue 1 (28th June 2022) - Yuan, Zheng-Nan; Sun, Zhi-Bo; Yu, Xin-Yi; Cheng, Ming; Cheng, Yue-chu; Li, An-ran; Vashchenko, Valerii; Kwok, Hoi-Sing; Srivastava, Abhishek K.
Abstract : Here we disclose a fast (ON time ~50μs and OFF time‐25μs at 55°C), high‐contrast, continuous phase modulator without fringe field effect (FFE). The phase modulator using the Kerr effect of vertical aligned deformed helix ferroelectric liquid crystal (VADHFLC). Specifically, FFE is a long‐term problem for nematic liquid crystal (NLC). In this article, we are disclosing, for the 1st‐time found, that no FFE exists for VADHFLC, even for phase modulator with 1μm pixel pitch, which is an attractive feature for ultra‐high‐resolution display and photonic applications. Moreover, the Kerr constant is 88 nm/V 2, and the contrast ratio is larger than 1000:1. It is a promising candidate for high‐PPI AR/VR displays, wavelength selective switch (WSS), hologram, adaptive optics, and LiDARs.